Phase angle predicts physical function in older adults. (September 2020) - Matias, C.N.; Nunes, C.L.; Francisco, S.; Tomeleri, C.M.; Cyrino, E.S.; Sardinha, L.B.; Silva, A.M.
Highlights: Lower values of PhA were related with lower z-score values for functional fitness composite. Higher values of PhA are related with a better physical function. PhA predicts body strength, agility and dynamic balance in healthy older adults. Abstract: Background: Phase angle (PhA) is recognized as an indicator of cellular health and may be a useful marker of physical functions in geriatric populations. Aims: We aim to analyse the ability of the Phase angle (PhA) to predict the physical function in older adults. Method: 113 healthy older adults (67 female and 46 male) performed physical tests using the Fullerton Battery – Senior Fitness Test, to assess their physical fitness. Bioelectrical impedance spectroscopy was used to determine PhA at 50KHz and dual-energy x-ray absorptiometry to assess body composition. Results: PhA was positively associated with functional fitness composite, chair stand, arm curl and 6 min walk test and negatively related with chair sit-and-reach and 8-foot and go (p < 0.05). Even after adjusting for potential confounding variables such as age, sex and appendicular lean soft tissue, PhA showed an association with arm curl (ß = 0.23, p = 0.038), and 8-foot and go ( ß=-0.214, p = 0.042). Conclusions: Higher values of PhA are related with a better physical function. Regardless of sex, age, and skeletal muscle, PhA predicts body strength, agility and dynamic balance in healthy older adults.